Exploring Gender Effects in Intention to Islamic Mobile Banking Adoption: An empirical study - Muhammad Jamal Haider; Changchun Gao; Tayyaba Akram; Syed Talib Hussain (Arab Economic and Business Journal, 2018)
This study is aimed to explore the gender effects in the intention to adopt Islamic mobile banking. Data was analyzed using structural equation modeling (SEM) methodology on 243 participants from Pakistan. In the findings, researchers identified two different models for intention to adopt Islamic mobile banking. It is inferred that males are more task driven and desire for personality, value and status, so their intention is significantly impacted by perceived usefulness and perceived self-expressiveness. Whereas, females have found lack of IT knowledge and trust, therefore, their intention is significantly impacted by perceived credibility. Further, the perceived financial cost was found of no concern for both males and females and social norms influenced the adoption but there existed no significant gender differences. Managerial and practical implications along with limitations and future research suggestions of the study are also discussed.
Keywords: 330; Gender differences; Gender effects; Islamic banking; Islamic mobile banking; m-Banking adoption; Pakistan